(untitled) (Journal of Economic Additions, 2026)
This study assesses the feasibility of a digital platform to combat school bullying in Maghnia using mixed-methods research. Despite high bullying prevalence (54%), formal reporting remains low (17%), while logistic regression identifies willingness to pay as a key adoption predictor. Financial analysis for the realistic scenario (600 families) yields an NPV of +1.58m DZD, an IRR of 39.5%, and a 1.56 BCR, with a 19-month payback period and a 34.2% margin of safety. Ultimately, the platform proves both economically profitable and socially sustainable within the educational digital transformation framework. Jel Classification Codes: H52, I21, I28, L86, M15.